Heat Integration of ammonia cooling unit in to the purification process of fats and oils - Tovazhnyanskyy, Leonid; Kapustenko, Petro; Ulyev, Leonid; Boldyrev, Stanislav; Garev, Andrey (My University, 2007)
The majority of the enterprises of the food processing industry in Ukraine use the technological processes with refrigerating cycles. Basically it is ammonia refrigeration units. In most of such refrigeration units energy of the ammonia overheat after compression is not used and discharged to the environment through cooling system. After some modernization this energy can be utilized for heating of technological streams. It can be achieved by detailed inspection of technological streams system and heat integration of the ammonia unit into a heating system of the enterprise. In this work inspection of fining and deodorization process of vegetable oils has been conducted and the opportunity of heat integration of an existing ammonia refrigeration unit into technological process is considered. There are two options for using of heat from cooling and condensation of ammonia: without additional compression of ammonia; with additional compression of ammonia stream. In this paper both options are considered and comparison is given.
Keywords: ammonia cooling unit; purification process; fats; oils; compressor unit; heat integration; pinch; retrofit; payback period